Kontribusi Model Pembelajaran Project Based Learning Sebagai Akselerator Peningkatan Kompetensi Desain Motif Tekstil Siswa SMK Busana - Idawati, Latifa; Nurjanah, Nunung; Alfianto, Imam (Universitas Nahdlatul Ulama Blitar, 2024)
This article discusses the contribution of the Project-Based Learning (PjBL) Learning Model as an accelerator for increasing the textile motif design competency of Fashion Vocational High School (SMK) students. The focus is on the integration of PjBL in learning fashion design and production in vocational schools, which is considered important to prepare graduates to face the challenges of the dynamic fashion industry. The discussion includes the characteristics of textile motif design competencies, the literature study methods used, the findings, and the role of PjBL in increasing students' creativity, critical thinking, and cross-disciplinary skills. This article provides a comprehensive overview of how PjBL can improve the quality of vocational education, especially in developing the textile motif design competency of SMK Clothing students.